The Effectiveness Of Project-Based Learning With A Deep Learning Approach To IPAS Learning Outcomes - Alya Dillah; Nur Afni; Erwin Nurdiansyah (ALENA : Journal of Elementary Education, 2026)
The low learning outcomes of Natural and Social Sciences (IPAS) in elementary schools are largely influenced by learning practices that are still teacher-centered and have not encouraged students to think deeply. This study aims to (1) How to apply the Project Based Learning (PjBL) model with a Deep Learning approach, (2) How the learning outcomes of social studies students before and after the application of the model, and (3) test its effectiveness in improving the learning outcomes of social studies of class V students at UPT SPF SD Inpres Tangkala 1 Makassar City. The study used a quantitative approach with a pre-experimental one group pretest-posttest design, involving 18 students as research subjects. Data was collected through learning outcome tests, observation sheets, and documentation, then analyzed descriptively and inferentially using the Wilcoxon Signed Rank Test with the help of SPSS version 29. The results showed an increase in the average score from 40.00 in the pretest to 92.22 in the posttest. The Wilcoxon test yielded a Z-value of -3.725 with Asymp. Sig. (2-tailed) < 0.001 (p < 0.05), so H0 is subtracted and H1 is accepted. Observation of teacher and student activities reached the very good category with a percentage of 87.5% and 80%, respectively. These findings prove that the application of the PjBL model with a Deep Learning approach is effective in improving the learning outcomes of IPAS students in class V, because it encourages meaningful learning, mindful learning, and joyful learning in an integrated manner in the real project stage.